Analysis of the effect of the scorpion toxin AaH-II on action potential generation in the axon initial segment - Fatima Abbas; Laila Ananda Blömer; Hugo Millet; Jérôme Montnach; Michel De Waard; Marco Canepari (Scientific Reports, 2024)
Abstract The toxin AaH-II, from the scorpion Androctonus australis Hector venom, is a 64 amino acid peptide that targets voltage-gated Na+ channels (VGNCs) and slows their inactivation. While at macroscopic cellular level AaH-II prolongs the action potential (AP), a functional analysis of the effect of the toxin in the axon initial segment (AIS), where VGNCs are highly expressed, was never performed so far. Here, we report an original analysis of the effect of AaH-II on the AP generation in the AIS of neocortical layer-5 pyramidal neurons from mouse brain slices. After determining that AaH-II does not discriminate between Nav1.2 and Nav1.6, i.e. between the two VGNC isoforms expressed in this neuron, we established that 7 nM was the smallest toxin concentration producing a minimal detectable deformation of the somatic AP after local delivery of the toxin. Using membrane potential imaging, we found that, at this minimal concentration, AaH-II substantially widened the AP in the AIS. Using ultrafast Na+ imaging, we found that local application of 7 nM AaH-II caused a large increase in the slower component of the Na+ influx in the AIS. Finally, using ultrafast Ca2+ imaging, we observed that 7 nM AaH-II produces a spurious slow Ca2+ influx via Ca2+-permeable VGNCs. Molecules targeting VGNCs, including peptides, are proposed as potential therapeutic tools. Thus, the present analysis in the AIS can be considered a general proof-of-principle on how high-resolution imaging techniques can disclose drug effects that cannot be observed when tested at the macroscopic level.